Thermodynamic Constraints for the Utilization of CO2 - Müller, Karsten; Mokrushina, Liudmila; Arlt, Wolfgang (Chemie Ingenieur Technik, 2014)
The production of chemical compounds from carbon dioxide could be a way to reduce this major greenhouse gas and gain a cheap raw material base. A variety of potential reactions might be suitable from a chemical point of view, but the low energetic level of carbon dioxide leads to severe limitations of the thermodynamic equilibrium. Most carbon dioxide utilization reactions are therefore not meaningful for an implementation outside the laboratory. This article gives an overview of the potential reactions to produce fine chemicals from carbon dioxide and their thermodynamic feasibility.
Keywords: Carbon dioxide; Chemical utilization; Greenhouse gas mitigation; Reaction equilibrium; Thermodynamics